Studi Analisis Terhadap Prespektif KH Sahal Mahfudh Tentang Aids Sebagai Alasan Perceraian - Abdul Kholiq Syafa’at (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
AIDS (Acquired Immuno Deficiency Syndrome), which is seen as a deadly disease and some people also call it with disgusting diseases lately a matter of study in relation to divorce reasons. Using the literature review from KH Sahal Mahfudh's Perspective resulted in the conclusion that AIDS has eliminated or at least diminished the significance of a marriage that has social and individual nuances. Through the analysis of AIDS-related reasons for divorce perspective KH Sahal Mahfudh, obtained the conclusion that KH Sahal Mahfudh very visible in promoting mashlahah, from here it can be seen that KH Sahal Mahfudh looked at the mashlahah aspects as a reference in lawmaking by considering socio-cultural and the development problems encountered people as the hallmark of social fiqh thought but also by using nash as its base